Integrated oral-gut microbiota therapy: a novel perspective on preventing bacterial translocation for systemic disease management - Zhu, Jie; Jiang, Ziyi; Yu, Fangli; Gao, Linglin; Wang, Xiaomei; Wang, Qiang (Frontiers in Cellular and Infection Microbiology, 2025)
Oral dysbiosis increases the risk of oral diseases and systemic diseases, with many related conditions overlapping with systemic diseases triggered by gut dysbiosis. Studies have shown that the oral cavity serves as an endogenous reservoir for gut microbial strains, influencing the homeostasis of both oral and gut microbiota through interactions involving bacterial translocation, microbial metabolites, immune cells, and inflammatory factors. In specific disease contexts, certain microbial communities [e.g., Porphyromonas gingivalis (P.g), Fusobacterium nucleatum (F.n)], metabolites (e.g., short-chain fatty acids, gingipains), ligands (e.g., lipopolysaccharides, peptidoglycans), or host responses may vary. However, substantial evidence has firmly established the central role of microbiota in oral-gut crosstalk. These findings position the oral-gut axis as a potential causal mechanism linking systemic diseases. Compared with healthy non-cancer subjects, cancer patients exhibit significant differences in oral microbial abundance and diversity. For instance, F.n is associated with an increased risk of colorectal cancer(CRC), while Oribacterium and Fusobacterium may serve as potential biomarkers for hepatocellular carcinoma. Notably, oral pathogens or their metabolites can translocate along the oral-gut axis or due to certain oral activities (e.g., toothbrushing, tooth extraction), contributing to the initiation and progression of inflammation and tumorigenesis. For example, P.g can accumulate in the liver, where its fimbrial protein FimA binds to Toll-like receptor 2 (TLR2), complement receptor 3 (CR3), and CXC-chemokine receptor 4 (CXCR4), triggering various immune responses that promote the development of non-alcoholic fatty liver disease(NAFLD). This review systematically summarizes recent advances in understanding the role of the oral microbiota and the oral-gut axis in systemic diseases, along with their underlying pathological mechanisms. It particularly highlights the translational value of integrating oral and gut microbiota research, offering novel insights for the prevention and precision treatment of systemic disorders. The unique and heterogeneous microbiota within the oral microbiota and the oral-gut axis may serve as novel diagnostic biomarkers or therapeutic targets for diseases associated with oral and gut dysbiosis.